1997
DOI: 10.1111/j.1460-9568.1997.tb01683.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Amygdala Dopamine Levels Modulate Cocaine Self‐administration Behaviour in the Rat: D1 Dopamine Receptor Involvement

Abstract: Nucleus accumbens dopamine is often hypothesized as the critical factor for modulating cocaine self-administration. In the current study we examined the extent to which dopamine in the amygdala could contribute to cocaine intake behaviour and modify nucleus accumbens dopamine levels. Rats were trained to self-administer intravenous cocaine (1.5 mg/kg/injection) under a fixed-ratio reinforcement schedule in daily 3 h operant training sessions. In the first in vivo microdialysis experiment, extracellular dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 39 publications
(41 reference statements)
3
55
1
1
Order By: Relevance
“…This nucleus receives the densest dopaminergic innervation arising from the ventral tegmental area to the amygdaloid complex (Fallon and Ciofi 1992), and it is thought to play a role in the modulation of the reinforcing and discriminative stimulus properties of cocaine (Caine et al 1995;Hurd et al 1997;Callahan et al 1995). In addition, it represents an important part of the "extended amygdala," a proposed forebrain continuum bordered by the central nucleus of the amygdala and the shell of the nucleus accumbens, which includes portions of the substantia innominata and bed nucleus of stria terminalis (Alheid and Heimer 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This nucleus receives the densest dopaminergic innervation arising from the ventral tegmental area to the amygdaloid complex (Fallon and Ciofi 1992), and it is thought to play a role in the modulation of the reinforcing and discriminative stimulus properties of cocaine (Caine et al 1995;Hurd et al 1997;Callahan et al 1995). In addition, it represents an important part of the "extended amygdala," a proposed forebrain continuum bordered by the central nucleus of the amygdala and the shell of the nucleus accumbens, which includes portions of the substantia innominata and bed nucleus of stria terminalis (Alheid and Heimer 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it represents an important part of the "extended amygdala," a proposed forebrain continuum bordered by the central nucleus of the amygdala and the shell of the nucleus accumbens, which includes portions of the substantia innominata and bed nucleus of stria terminalis (Alheid and Heimer 1988). Several animal studies have suggested the "extended amygdala" as a neural substrate for the behavioral effects of self-administered cocaine (Robledo and Koob 1993;Caine and Koob 1994;Hurd et al 1997;McGregor and Roberts 1993;Robbins et al 1989;Robledo et al 1996). In humans, recent evidence from brain-imaging studies suggest a role for dopamine-rich brain regions, including the nucleus accumbens and amygdala, in cocaine craving (Grant et al 1996;Breiter et al 1997;Childress et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the cocaine-induced increase in the synthesis and/or release of CRH in this region may mediate some of the behavioral effects of the drug. In fact, a role for the amygdala in psychomotor stimulant self-administration (Deminiére et al 1988;Caine et al 1995;Hurd et al 1997) and relapse to drug seeking (Baker et al 1999) has already been established. Interestingly, this role appears to at least partially involve the classical conditioning of drug effects (Whitelaw et al 1996;Meil and See 1997), a process that is obviously intimately involved in the persistence and relapse of cocaine-seeking behavior and may also be related to the ability of CP-154,526 to reduce cocaine self-administration even during the first few minutes of the behavioral session.…”
Section: Discussionmentioning
confidence: 99%
“…Cocaine reinforcement and cocaine-induced behavioral sensitization depend upon the activation of dopaminergic and glutamatergic neurotransmission (especially via NMDA receptors) in the ventral tegmental area (VTA), nucleus accumbens (N.Acc), and prefrontal cortex (PFC) (Goeders & Smith, 1983Hurd et al, 1997;Pulvirenti et al, 1992;Ritz et al, 1987Ritz et al, ,1988Roberts & Koob, 1982;Vanderschuren & Kalivas, 2000;Volkow et al, 1997aVolkow et al, ,1997bWolf, 1998;White et al, 1995;Zhang et al, 1997). The differences we previously observed between the brief and extended access group were also found within either the N.Acc and/or PFC (i.e.…”
Section: Introductionmentioning
confidence: 99%